2014
DOI: 10.1177/1936724414528181
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Responses to School Violence in Cape Town, South Africa

Abstract: Although researchers have been interested in the psychological impact of school and community violence on children in South Africa, little work has been done on the effects of exposure to school violence on teachers. de Wet's exploratory study of South African teachers and administrators is an exception, although her focus was on student bullying of school personnel that included violence, rather than violence per se. Because there is so little research on the impact of school violence on educators in South Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
4
0
4
Order By: Relevance
“…Skoolbendes is egter nie net 'n Kaapse probleem nie. Dit kom ook in ander provinsies soos Gauteng en Kwazulu-Natal voor (De Wet, 2016, Shields, Nadasen & Hanneke, 2015.…”
Section: Inleidingunclassified
See 2 more Smart Citations
“…Skoolbendes is egter nie net 'n Kaapse probleem nie. Dit kom ook in ander provinsies soos Gauteng en Kwazulu-Natal voor (De Wet, 2016, Shields, Nadasen & Hanneke, 2015.…”
Section: Inleidingunclassified
“…Daar is veskeie redes waarom skoliere aan bendes behoort. Die belangrikste redes waarom hulle by bendes aansluit, is volgens verskeie navorsingstudies, 'n behoefte aan identiteit, groepsdruk asook ekonomiese redes, soos die basiese behoeftes aan kos en klere en om veilig te voel in hul gemeenskappe (Magidi, 2014;Pertus & Kinnes, 2019;Pinnock & Doughlas-Hamilton, 1997;Shields et al, 2015;Van der Merwe & Swanepoel, 2017;Wijnberg, 2012).…”
Section: Inleidingunclassified
See 1 more Smart Citation
“…La mayor parte de los estudios empíricos que consideran a los profesores y otros integrantes del personal de la escuela (school staff) preguntan a éstos su percepción sobre el nivel de violencia entre estudiantes (Bradshaw, Sawyer, & O´Brennan, 2007) o bien, la violencia o victimización que ellos reciben por parte de los estudiantes (Shields, Nadasen, & Hanneke, 2015). Son pocos los estudios que preguntan a los estudiantes por el nivel de victimización que reciben por parte de sus profesores o personal del centro escolar.…”
Section: Victimización De Estudiantes Desde El Personal De La Escuelaunclassified
“…A number of examples attest to learners' experiencing school as an authoritarian encounter. Although corporal punishment is illegal in South African schools, it continues to be used by teachers (Shields, Nadasen and Hanneke 2014). It has been found that principals dominate decisionmaking in South African schools while learner participation is moderate (Mncube and Harber 2013: 23-24).…”
Section: A Catalyst For School Violencementioning
confidence: 99%